2018
DOI: 10.3389/fpsyg.2018.02353
|View full text |Cite
|
Sign up to set email alerts
|

The Assertive Resolution of Conflicts in School With a Gamified Emotion Education Program

Abstract: Coexistence in schools inevitably carries a higher risk of conflicts among peers. This fact can be detrimental to the well-being and academic achievement of the students. In many developed countries, about 90% of the pupils in compulsory secondary education report witnessing assaults among peers. In this regard, recognizing, controlling and managing emotions is key to ensure a healthy and effective interaction with others. Negative emotions, such as anger, can trigger conflicts or even episodes of violence if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…To address this interaction, knowledge is required to generate resolution and prevention tools for the accelerated growth of conflicts experienced by educational institutions in many countries around the world (Filella et al, 2018), contemplating the different factors involved. This study proposes a model aimed at facilitating the development of resources for teachers that allow them to improve the management of the different conflict situations that arise in the context of the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To address this interaction, knowledge is required to generate resolution and prevention tools for the accelerated growth of conflicts experienced by educational institutions in many countries around the world (Filella et al, 2018), contemplating the different factors involved. This study proposes a model aimed at facilitating the development of resources for teachers that allow them to improve the management of the different conflict situations that arise in the context of the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Extended Process Model of Emotional Regulation proposed by Gross (2015), it is indicated that the emergence of emotions -and other affective states-occur as a result of a series of evaluations that individuals perform. For example, negative emotions, such as anger, can trigger conflicts or even episodes of violence if they are not regulated properly (Fritz et al, 2015;Filella et al, 2018). This process begins with a given situation (entry), which is perceived by the person in a subjective way.…”
Section: Emotional Regulationmentioning
confidence: 99%
See 3 more Smart Citations